Comparison of the effects of 7.2% hypertonic saline and 20% mannitol on whole blood coagulation and platelet function in dogs with suspected intracranial hypertension - a pilot study - Yozova ID; Howard J; Henke D; Dirkmann D; Adamik KN (BioMed Central)
Hyperosmolar therapy with either mannitol or hypertonic saline (HTS) is commonly used in the treatment of intracranial hypertension (ICH). In vitro data indicate that both mannitol and HTS affect coagulation and platelet function in dogs. The aim of this study was to compare the effects of 20% mannitol and 7.2% HTS on whole blood coagulation using rotational thromboelastometry (ROTEM®) and platelet function using a platelet function analyzer (PFA®) in dogs with suspected ICH. Thirty client-owned dogs with suspected ICH needing osmotherapy were randomized to receive either 20% mannitol (5 ml/kg IV over 15 min) or 7.2% HTS (4 ml/kg IV over 5 min). ROTEM® (EXTEM® and FIBTEM® assays) and PFA® analyses (collagen/ADP cartridges) were performed before (T0), as well as 5 (T5), 60 (T60) and 120 (T120) minutes after administration of HTS or mannitol. Data at T5, T60 and T120 were analyzed as a percentage of values at T0 for comparison between groups, and as absolute values for comparison between time points, respectively.No significant difference was found between the groups for the percentage change of any parameter at any time point except for FIBTEM® clotting time. Within each group, no significant difference was found between time points for any parameter except for FIBTEM® clotting time in the HTS group, and EXTEM® and FIBTEM® maximum clot firmness in the mannitol group. Median ROTEM® values lay within institutional reference intervals in both groups at all time points, whereas median PFA® values were above the reference intervals at T5 (both groups) and T60 (HTS group).Using currently recommended doses, mannitol and HTS do not differ in their effects on whole blood coagulation and platelet function in dogs with suspected ICH. Moreover, no relevant impairment of whole blood coagulation was found following treatment with either solution, whereas a short-lived impairment of platelet function was found after both solutions.
Keywords: Intracranial hypertension; Osmotherapy; Hypertonic saline; Mannitol; Hemostasis; Thromboelastometry; Platelet function; 0601 Biochemistry and Cell Biology; 0605 Microbiology; 0707 Veterinary Sciences